Efficacy of Trials of Improved Practices (TIPs) Approach and Partial Processing on Household Utilization of Legumes: A Case Study of Ntcheu and Dedza Districts - Ministry of Agriculture, Irrigation and Water Development; Lilongwe University of Agriculture & Natural Resources; Michigan State University (International Food Policy Research Institute, 2017)
This data contains data produced from cross-sectional survey and lab experiment on shelf life of processed legume.